Dirt of the Swamp and Gold of the Oil: Strategies of the Soviet Literary “Colonization” of the Swamps of Siberia - Снежко, Юлия (Literatūra, 2022)
The article explores the specifics of the literary rhetoric of the “colonization” of the swamps of Western Siberia and oil. It shows how the attitude to the swamp space is constructed (through its abstraction, mapping and poetics of the straight line), how the differences between the substances of the swamp and oil are established (stickiness, viscosity, alluring, femininity), and the ways of constructing the collective Soviet subject (ideas of modernization, sublimation, hybridization of the language of the indigenous population and oil workers) are also investigated basing on Soviet prose of the 1960s–1980s. The article concludes about the dominant, mostly negative attitude towards the swamp (as opposed to oil), because of the instrumental approach to this landscape and predominant soviet discourse of progress.
Keywords: swamp; oil; soviet literature; postcolonialism; ecocriticism